Improving the Security of Secret Questions using Smartphone Sensor and App Data - Joshi, Prabin; Sadashiv, Naidila; Gyawali, Bivek; Simkhada, Sudeep (International Journal of Computer Sciences and Engineering, 2019)
Security and privacy is an important topic in the field of sensitive data communication. Secondary authentication methods like secret questions are widely used as a form of authentication which can be easily guessed. Moreover, users may forget his/her answers, and even if a user remembers the answer, they can forget how it was written. The recent prevalence of smartphone has provided a rich source of personal data concerning the user’s knowledge of its short-term history. Such a feature has made it possible for people to spend more and more time on these devices. Furthermore, the popularity of social media applications and single sign-on increases day after day, users with their information do not always take as many precautions as they need. We present a “Secret-Question based Authentication System” having a set of secret questions based on user’s short-term smartphone usage. We have developed prototype of android application, and have evaluated the security of the secret questions. We also present a multifactor authentication that creates more and more walls to prevent people from seeing your information. It allows the verification of user’s identity for a login or other transaction-based on more than one method of authentication from independent categories of credentials.